Yezidism between scholarly literature and actual practice: from "heterodox" Islam and "syncretism" to the formation of a transnational Yezidi "orthodoxy" : originally lecture AAR 2009 Montréal - Langer, Robert (British journal of Middle Eastern studies, 2010)
This paper examines the question of heterodoxy and orthodoxy from the point of view of the Yezidis, attempting to consider their place vis-a-vis Islam and at the same time make a valid general characterisation of their form of social life. It is particularly interested in the transition from the rural background to urban European cities by the Yezidi community, and concludes that there is a strong chance that the need to interact with European society will force a codification of doctrine upon the Yezidis, with effects which are not yet clear.
Gesehen am 23.02.2021